Mengenal Spina Bifida dan Pencegahannya - Faesal Atsani, Genta; Mauly Ilawanda, Zanetha; Fahira Basyir, Ilma (Jurnal Syntax Fusion, 2021)
Neural tube defects (NTD) are one of the birth defects or congenital abnormalities that occur in the brain and spine, and commonly find in newborns worldwide. Anencephaly and spina bifida are the two prevalent forms of NTD. The incidence of spina bifida happen on average 1 in 1000 cases of birth worldwide and there are 140,000 cases per year worldwide. Source searches were carried out on the online portal of journal publications as many as 20 sources from MedScape, Google Scholar and the Nation Center for Biotechnology Information / NCBI with the keywords “Neural tube defects (NTD), prevention, and spina bifida”. Spina bifida is a congenital abnormality that occurs in the womb due to a failure of closing process the neural tube during the first few weeks of embryonic development which causes the spine not completely close around the developing spinal cord nerves. NTD can ensue multifactorial conditions such as genetic, environmental, and folate deficiency. The use of folic acid supplementation starting at least 3 months before pregnancy, those are 400 mcg (0.4 mg) per day and 800 mcg per day during pregnancy can reduce the risk of developing neural tube defects such as spina bifida. Generally, spina bifida is undertaking by surgery and the regulation of patients comorbid. Public can find out prevention to avoid or reduce the risk of spina bifida so that the incidence of spina bifida can decrease along with the increasing awareness of the community regarding this disease.